REKONSTRUKSI SISTEM PEMUNGUTAN PAJAK PENGHASILAN (PPH) BADAN BERBASIS NILAI KEADILAN - Amin Purnawan (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Fairness in taxation policy can be viewed from: first, the equilibrium relationship between tax authorities and taxpayers, secondly, equitable allocation of the tax burden on various segments of society according to his ability. Corporate income tax collection system did not reflect the sense of justice because the application of the single rate system of corporation tax burden caused injustice, and the authority of the tax authorities are still too broad. It needs political reconstruction based corporate income tax law of justice based on Pancasila, through structuring and strengthening aspects of philosophy, the subtance and structure of tax law. Progressive tax law by using a new paradigm is expected to display the figure of taxation more equitable and humane, so as to promote awareness of voluntary compliance from tax payer, followed by transparency and responsibility of countries to achieve people’s welfare. Keywords: Reconstruction, Corporate Income Taxes, Juctice